Distribution of Glycan Motifs at the Surface of Midgut Cells in the Cotton Leafworm (Spodoptera littoralis) Demonstrated by Lectin Binding - Walski, Tomasz; De Schutter, Kristof; Cappelle, Kaat; Van Damme, Els J. M.; Smagghe, Guy (Frontiers in Physiology, 2017)
Glycans are involved in many biological phenomena, including signal transduction, cell adhesion, immune response or differentiation. Although a few papers have reported on the role of glycans in the development and proper functioning of the insect midgut, no data are available regarding the localization of the glycan structures on the surface of the cells in the gut of insects. In this paper, we analyzed the spatial distribution of glycans present on the surface of the midgut cells in larvae of the cotton leafworm Spodoptera littoralis, an important agricultural pest insect worldwide. For this purpose, we established primary midgut cell cultures, probed these individual cells that are freely suspended in liquid medium with a selection of seven fluorescently labeled lectins covering a range of different carbohydrate binding specificities [mannose oligomers (GNA and HHA), GalNAc/Gal (RSA and SSA), GlcNAc (WGA and Nictaba) and Neu5Ac(α-2,6)Gal/GalNAc (SNA-I)], and visualized the interaction of these lectins with the different zones of the midgut cells using confocal microscopy. Our analysis focused on the typical differentiated columnar cells with a microvillar brush border at their apical side, which are dominantly present in the Lepidopteran midgut and function in food digestion and absorption, and as well as on the undifferentiated stem cells that are important for midgut development and repair. Confocal microscopy analyses showed that the GalNAc/Gal-binding lectins SSA and RSA and the terminal GlcNAc-recognizing WGA bound preferentially to the apical microvillar zone of the differentiated columnar cells as compared to the basolateral pole. The reverse result was observed for the mannose-binding lectins GNA and HHA, as well as Nictaba that binds preferentially to GlcNAc oligomers. Furthermore, differences in lectin binding to the basal and lateral zones of the cell membranes of the columnar cells were apparent. In the midgut stem cells, GNA and Nictaba bound more strongly to the membrane of these undifferentiated cells compared to the microvillar pole of the columnar cells, while SSA, HHA, WGA and SNA-I showed stronger binding to the microvilli. Our results indicated that polarization of the midgut cells is also reflected by a specific distribution of glycans, especially between the basal and